10.1016/s1544-8800(05)70455-3 (CrossRef Listing of Deleted DOIs, 2000)
Pain is a key determinant of quality-of-life following breast cancer surgery, the most common cancer operation in the United States. Gabapentinoids are frequently prescribed for pain management, yet their respiratory, cardiovascular, and opioid-related adverse effects remain unclear. This target trial emulation, analyzing US commercial claims (2013-2023), evaluated these safety outcomes under gabapentin-opioids initiation vs. opioids only during the first postoperative month following breast cancer surgery, with sustained 1-year follow-up. Women with nonmetastatic breast cancer were eligible on surgery dates if they had no prior outcomes, nor gabapentinoids or opioid prescriptions. Outcomes included time-to-first respiratory complications, major adverse cardiovascular events (MACE), arrhythmia, and high-dose opioid utilization (≥ 50 or ≥ 90 morphine -milligram equivalent [MME]). We estimated 1-year outcome risks and 95% CIs under gabapentin-opioids and opioids-only strategies using weighted pooled logistic regressions with bootstrapping, including stabilized inverse probability weighting to adjust for baseline and time-varying confounders. Of 86,290 eligible individuals, 1709 initiated gabapentin and opioids, and 39,372 initiated opioids only. Risks of respiratory complications (RR 1.24, 95% CI: 0.26-3.02), MACE (RR 0.95, 95% CI: 0.31-1.85), and arrhythmia (RR 0.65, 95% CI: 0.24-1.33) were comparable under gabapentin-opioids and opioids-only. Risk of receiving opioid dosage ≥ 50 MME (RR 1.23, 95% CI: 0.85-1.72) and ≥ 90 MME (RR 1.09, 95% CI: 0.43-2.23) were comparable. This study challenged the limited evidence regarding safety concerns of adding gabapentin for pain management, finding that gabapentin-opioids initiation carried comparable respiratory and cardiovascular risks to opioids only following breast cancer surgery. However, we did not find evidence that adjunctive gabapentin reduces subsequent high-dose opioid utilization.